If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(3b + 1) + 10 = 53 Reorder the terms: -9(1 + 3b) + 10 = 53 (1 * -9 + 3b * -9) + 10 = 53 (-9 + -27b) + 10 = 53 Reorder the terms: -9 + 10 + -27b = 53 Combine like terms: -9 + 10 = 1 1 + -27b = 53 Solving 1 + -27b = 53 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -27b = 53 + -1 Combine like terms: 1 + -1 = 0 0 + -27b = 53 + -1 -27b = 53 + -1 Combine like terms: 53 + -1 = 52 -27b = 52 Divide each side by '-27'. b = -1.925925926 Simplifying b = -1.925925926
| 2x+2y=112 | | M-5m+2m-4= | | 12y+2=21y+13 | | 9x-5+9-5x= | | 18X-4X= | | 38.6=j-28.8 | | 12x+2=4x-1 | | 8+e=1e+5e-50 | | 6y+1=31y+13 | | (x^2)-(4x)+(2)=0 | | 2(x+3)+8=5x-3(-4+x) | | e-11.7=37.1 | | 8x^2-16x+80=0 | | 10y+2=81 | | 11x+77=-63+6x | | 0.02(y-8)+0.20y=0.14y-0.7 | | 10000x=80+4x+0.1x^2 | | -7(3x-1)=-91 | | 6(20-5)= | | p-4.9=24.9 | | 27-15=3(37+2x) | | 3m+1=2m | | 0.4x-0.9x-19=1 | | 0.12(0.04)= | | 9x-y+1=0 | | 4x^2+5x=11 | | 2x-1-x=-2 | | 5b+6-64+2=19 | | 2x+9/6=11 | | j-18.5=19.6 | | -51k=65 | | 2x(18x+1)=2x+25 |